KOMPETENSI GURU: FAKTOR PENGHAMBAT IMPLEMENTASI PROJEK PENGUATAN PROFIL PELAJAR PANCASILA - Asvio, Nova; Sriwahyuni, Eci; Rahmadoni, Jefril; Sugianto, Sugianto; Mindani, Mindani; Wulandari, Isnain (UIN Imam Bonjol Padang, 2023)
Pancasila students are a subset of Indonesian students who have global competence and character as defined by Pancasila values across six major dimensions. This study is a literature review that employs the SLR method, which consists of six stages: planning, literature search, criteria assessment (inclusion and exclusion), quality assessment, data collection, and data analysis. The purpose of this research is to learn about the history, steps, and challenges associated with implementing P5. The data analysis results show that P5 implementation is carried out to produce Indonesian students who are competent, have character, and behave in accordance with Pancasila values. P5 consists of four steps: 1) Understanding the Independent Curriculum Outline; 2) Understanding Learning and Assessment; 3) Recognize the evolution of the educational unit's operational curriculum in the Independent Curriculum; and 4) Recognize the evolution of a project to strengthen the Pancasila student profile. Obstacles to implementing P5 are more prevalent in teachers, who are the primary component in shaping the character of Indonesian students.